Pemberdayaan Kader Dalam Penanggulangan Masalah Kesehatan Intelegensia Pada Lansia Akibat Gangguan Degeneratif Di Wilayah Kerja Puskesmas Gamping I, Sleman - Wahyu Ratna; Ida Mardalena; Induniasih Induniasih (POLTEKKES KEMENKES YOGYAKARTA, 2017)
One of the most feared man when he began to ripen is becoming senile and difficulty remembering recent memory. Someone who has dementia, there will be a decrease in intellectual function that causes the deterioration cognition and functional, resulting in impaired function of thesocial, work and daily activities, therefore their social activities will also be affected. Activities to increase the intelligence of the elderly can be done in Posyandu and at home. Posyandu kader are trained to conduct simple screening and intervention for at Posyandu and can be continued at home. During these elderly who come to Posyandu only get a health screening and supplementary feeding alone. This study aims to look at the role of Posyandu kader in improving intelligence elderly. The study is a quasi experiment, pre- post with control design. Samples taken as many as 32 elderly people from each of posyandu Gejawan Kulon as the intervention group and posyandu Gejawan Wetan as the control group. The results showed that the characteristics of the most respondents are aged 60-69 as much as 38,7% in intervention group and 71,9% in control group, female 100% in intervention group and 78,1% in control group, as housewives 50% in intervention group and 59,4% in the control group. And has last education in elementary school 50% in intervention group and 43,7% in control group, level of intelligence on the second assessment 62,5% normal-light in intervention group and balanced between normal-light and moderate in control group. And the number of eldery who have intelegensia reduction decreased by 0,3 from the current first assessment based on the T-Test as result 1,4 from 1,7. The Conclusion is the influence in intelligence enhancement training kader to increased intelligence eldery evidenced by the decline in the number of eldery who experience a decrease in intelligence in the control group.